Battery, positive electrode sheet, preparation method thereof, and power-using device

By adopting a two-layer active layer structure in the positive electrode sheet of lithium-ion battery, combining the ternary material A with a larger particle size and lithium iron phosphate material, and the ternary material B with a smaller particle size, the problem of large cyclic expansion force and increased cyclic impedance in the medium and low SOC is solved, and higher energy density, cyclic performance and power performance stability are achieved.

CN118888686BActive Publication Date: 2025-03-04CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411347314.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-03-04
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have large cyclic expansion force and increased cyclic impedance DCR under medium and low SOCs, resulting in deterioration of power performance stability.

Method used

The structure design of two layers of positive electrode active layer is adopted. The first layer of the lower layer of the first positive electrode active layer contains a ternary material A with a larger particle size and a lithium iron phosphate material with a smaller particle size. The second upper layer of the positive electrode active layer contains a ternary material B, which improves compaction density and electrical conductivity through the combination of particle size and type.

Benefits of technology

The energy density, cycle performance and power performance stability of the battery are improved, making up for the disadvantage of the rapid increase in DCR of a single ternary material at low SOC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888686B_ABST
    Figure CN118888686B_ABST
Patent Text Reader

Abstract

The present application provides a battery, a positive electrode plate, a preparation method thereof, and an electric device. The battery includes a positive electrode plate, the positive electrode plate includes: a positive current collector; a first positive active layer, arranged on at least one surface of the positive current collector, the first positive active layer includes a ternary material A and a lithium iron phosphate material, the Dv50 particle size of the ternary material A is greater than the Dv50 particle size of the lithium iron phosphate material; and / or, the Dn50 particle size of the ternary material A is greater than the Dn50 particle size of the lithium iron phosphate material; and a second positive active layer, arranged on the surface of the first positive active layer away from the positive current collector, the second positive active layer includes a ternary material B. The battery is applied with the above-mentioned positive electrode plate, which can improve the energy density, cycle performance and power performance stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery, a positive electrode plate, a preparation method thereof, and an electrical device. Background Art

[0002] In recent years, secondary batteries such as lithium-ion batteries have made great progress, so their application scope is becoming more and more extensive. For example, secondary batteries such as lithium-ion batteries can be widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, so their energy density, cycle performance and power performance stability are also put forward higher requirements. Summary of the invention

[0003] Based on this, it is necessary to provide a battery, a positive electrode plate and a preparation method thereof and an electrical device, aiming to improve the energy density, cycle performance and power performance stability of the battery.

[0004] The present application is implemented through the following technical solutions.

[0005] In a first aspect of the present application, a battery is provided, comprising a positive electrode sheet, wherein the positive electrode sheet comprises:

[0006] Positive electrode current collector;

[0007] A first positive electrode active layer is provided on at least one surface of the positive electrode current collector, wherein the first positive electrode active layer comprises a ternary material A and a lithium iron phosphate material, wherein the Dv50 particle size of the ternary material A is larger than the Dv50 particle size of the lithium iron phosphate material, and / or the Dn50 particle size of the ternary material A is larger than the Dn50 particle size of the lithium iron phosphate material; and,

[0008] A second positive electrode active layer, disposed on a surface of the first positive electrode active layer away from the positive electrode current collector, wherein the second positive electrode active layer comprises a ternary material B;

[0009] Wherein, both the ternary material A and the ternary material B include nickel element, and the molar content of the nickel element in the ternary material A in the total amount of the ternary metal is higher than the molar content of the nickel element in the ternary material B in the total amount of the ternary metal.

[0010] Ternary materials have the advantage of high energy density when used in batteries, but they have some problems at medium and low SOC (state of charge), including large cycle expansion force and increased cycle impedance DCR, which leads to a significant deterioration in power performance.

[0011] Therefore, the present application adopts a two-layer positive electrode active layer structure design and adopts a mixed system of lithium iron phosphate and ternary materials. At higher SOC, it is mainly the ternary material that provides lithium ions for discharge, and at low SOC, it is mainly lithium iron phosphate that provides lithium ion discharge. The second positive electrode active layer of the upper layer adopts ternary material B to provide good energy density, and the lithium ion transmission speed of the ternary material is fast. The ternary material B is located in the second positive electrode active layer of the upper layer and can provide good cycle performance. On this basis, the first positive electrode active layer of the lower layer adopts ternary material A with a larger particle size and lithium iron phosphate material with a smaller particle size. The mixed gradation of two positive electrode active materials with different particle sizes and different types can improve the compaction density of the first positive electrode active layer, so that the lower layer and the upper positive electrode active layer have a good compaction density match to give full play to the energy density advantage of the ternary material. At the same time, lithium iron phosphate is added to the first positive electrode active layer of the lower layer. Lithium iron phosphate has an olivine structure, and its lattice structure is stable and not easy to collapse and cause material loss. Therefore, the cycle impedance of the first positive electrode active layer of the lower layer is low, and because the voltage platform of lithium iron phosphate is lower, thanks to the elongation of the Fe platform, the power performance of the battery in the medium and low SOC state is significantly improved, which makes up for the disadvantage that the battery uses a single ternary material and the DCR increases rapidly in the low SOC state.

[0012] Ternary materials with higher nickel content have higher specific capacity. The increase in nickel content can improve the reversible lithium insertion capacity of the ternary material, thereby increasing the energy density of the battery. However, as the nickel content of the ternary material increases, its alkalinity increases, its water absorption increases, and its side reactions increase, which will also lead to an increase in DCR. Further setting the ternary material A with a higher nickel content in the first positive electrode active layer of the lower layer can make up for the problem of increased DCR caused by the higher nickel content of the ternary material A, so as to improve the energy density while taking into account good power performance. Ternary material B with a lower nickel content has a better advantage in high voltage resistance, and has fewer side reactions than high-nickel ternary materials, which is beneficial to reduce the DCR of the battery.

[0013] Therefore, the above-mentioned positive electrode plate of the present application is applied to a battery, which can make the battery have good energy density, cycle performance and power performance stability.

[0014] In some embodiments, at least one of the following features is met:

[0015] (1) The Dv50 particle size of the ternary material A is 2 μm to 5.2 μm, and / or the Dn50 particle size of the ternary material A is 2 μm to 7.2 μm;

[0016] (2) The ternary material A comprises polycrystalline particles;

[0017] (3) The difference between the Dv50 particle size of the ternary material A and the Dv50 particle size of the lithium iron phosphate material is in the range of 0.8 μm to 4 μm.

[0018] The Dv50 particle size or Dn50 particle size of the ternary material A is within the above range, so that the gaps between the ternary material particles in the first positive electrode active layer are within a relatively suitable range, the impedance of lithium ions inside the positive electrode active material particles is low and the positive electrode active layer has a suitable compaction density, thereby improving the conductivity and compaction density of the positive electrode active layer, thereby enabling the battery to further have good energy density, cycle performance and power performance.

[0019] In some embodiments, the Dv50 particle size of the ternary material A is 3 μm to 4.2 μm, and / or the Dn50 particle size of the ternary material A is 3 μm to 6.2 μm.

[0020] In some embodiments, at least one of the following features is met:

[0021] (1) The Dv50 particle size of the lithium iron phosphate material is 0.8 μm to 1.8 μm, and / or the Dn50 particle size of the lithium iron phosphate material is 0.8 μm to 3.8 μm;

[0022] (2) The lithium iron phosphate material includes single crystal particles;

[0023] (3) The lithium iron phosphate material includes one or more of lithium iron phosphate bulk particles, lithium iron phosphate bulk particles coated by a coating layer, and their respective doping and modification materials.

[0024] The Dv50 particle size or Dn50 particle size of the lithium iron phosphate material is within the above range, and it is matched with the ternary material A in the above particle size range, so that the small particle size lithium iron phosphate material can be more fully filled in the gap between the large particles, which can further improve the compaction density of the lower layer and make the compaction density between the lower active layer and the upper active layer better matched. In addition, the Dv50 particle size of the lithium iron phosphate material is within the above smaller Dv50 range, Li + The smaller the transmission path, the more conductive the first cathode active layer can be, the better the battery's kinetics, especially its power performance at low and medium SOCs, and the more powerful the battery, so that the battery has good energy density, cycle performance, and power performance.

[0025] Lithium iron phosphate materials include single crystal particles. Since the single crystal particles have a perfect crystal structure or few defects, the migration resistance of lithium ions in the solid phase of the single crystal particles is small, which can reduce the solid phase impedance and thus improve the power performance of the battery.

[0026] In some embodiments, the Dv50 particle size of the lithium iron phosphate material is 1.0 μm to 1.5 μm, and / or the Dn50 particle size of the lithium iron phosphate material is 1 μm to 3.5 μm.

[0027] In some of the embodiments, in the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 50% to 95%.

[0028] In some of the embodiments, in the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 60% to 80%.

[0029] The mass proportion of lithium iron phosphate material is within the above range, so that more lithium iron phosphate material can be more fully filled in the gaps between large particles, and the role of lithium iron phosphate in reducing DCR under medium and low SOC during its life cycle can be better exerted, thereby improving the power performance of the battery.

[0030] In some embodiments, at least one of the following features is met:

[0031] (1) The Dv50 particle size of the ternary material B is 4 μm to 13 μm, and / or the Dn50 particle size of the ternary material B is 4 μm to 15 μm;

[0032] (2) The ternary material B includes single crystal particles.

[0033] The Dv50 particle size or Dn50 particle size of the ternary material B in the upper second positive electrode active layer is within the above range, so that the gaps between the ternary material particles in the second positive electrode active layer are within a relatively suitable range, the impedance of lithium ions inside the positive electrode active material particles is low and has a suitable compaction density, thereby improving the conductivity and compaction density of the second positive electrode active layer, thereby enabling the battery to further have good energy density, cycle performance and power performance; in addition, the battery can also achieve 4C fast charging performance while having a good cycle life.

[0034] In some embodiments, the Dv50 particle size of the ternary material B is 8 μm to 11 μm, and / or the Dn50 particle size of the ternary material B is 8 μm to 13 μm.

[0035] In some embodiments, at least one of the following features is met:

[0036] (1) The thickness of the first positive electrode active layer is between 15 μm and 150 μm;

[0037] (2) The thickness of the second positive electrode active layer is between 20 μm and 200 μm.

[0038] In some embodiments, the thickness of the first positive electrode active layer is less than the thickness of the second positive electrode active layer.

[0039] In this way, the second positive electrode active layer is the main one and the first positive electrode active layer is the auxiliary one. The second positive electrode active layer in the upper layer is used as the main active layer to provide the main performance of high energy density and cycle performance of the battery cell; the first positive electrode active layer in the lower layer is used as the auxiliary one. When the battery cell is discharged at a low SOC, since the second positive electrode active layer in the upper layer is close to a fully embedded state, the main lithium embedding process is in the first positive electrode active layer in the lower layer. The kinetics of the first positive electrode active layer in the lower layer directly affects the low SOC power of the battery cell. Therefore, the thickness of the first positive electrode active layer in the lower layer is controlled to be smaller, and the kinetics of the first positive electrode active layer in the lower layer are improved. With the use of the battery, the SOC kinetic advantage (low impedance) of the positive electrode sheet will become more and more obvious, reducing the DCR at medium and low SOC during the life cycle, thereby improving the power performance of the battery.

[0040] In some embodiments, at least one of the following features is met:

[0041] (1) The thickness of the first positive electrode active layer is between 30 μm and 60 μm;

[0042] (2) The thickness of the second positive electrode active layer is between 70 μm and 100 μm.

[0043] In some embodiments, the ternary material A and the ternary material B each independently include at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material.

[0044] In some embodiments, the nickel-cobalt-manganese ternary material includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.5 Co 0.25 Mn 0.25 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.68 Co 0.10 Mn 0.22 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2;

[0045] The nickel-cobalt-aluminum ternary material includes LiNi 0.8 Co 0.15 Al 0.05 O2.

[0046] In some embodiments, at least one of the following features is met:

[0047] (1) The molar content of nickel in the ternary material A is between 33% and 90% of the total amount of the ternary metal;

[0048] (2) The molar content of nickel in the ternary material B is between 33% and 90% of the total amount of the ternary metal.

[0049] In some embodiments, at least one of the following features is met:

[0050] (1) The molar content of nickel in the ternary material A is between 70% and 90% of the total amount of the ternary metal;

[0051] (2) The molar content of nickel in the ternary material B is between 33% and 50% of the total amount of the ternary metal.

[0052] In a second aspect of the present application, a positive electrode sheet is provided, comprising:

[0053] Positive electrode current collector;

[0054] A first positive electrode active layer is provided on at least one surface of the positive electrode current collector, wherein the first positive electrode active layer comprises a ternary material A and a lithium iron phosphate material, wherein the Dv50 particle size of the ternary material A is larger than the Dv50 particle size of the lithium iron phosphate material, and / or the Dn50 particle size of the ternary material A is larger than the Dn50 particle size of the lithium iron phosphate material; and,

[0055] A second positive electrode active layer, disposed on a surface of the first positive electrode active layer away from the positive electrode current collector, wherein the second positive electrode active layer comprises a ternary material B;

[0056] Wherein, both the ternary material A and the ternary material B include nickel element, and the molar content of the nickel element in the ternary material A in the total amount of the ternary metal is higher than the molar content of the nickel element in the ternary material B in the total amount of the ternary metal.

[0057] In a third aspect of the present application, a method for preparing a positive electrode sheet is provided. The positive electrode sheet is the positive electrode sheet provided in the first aspect above. The preparation method comprises the following steps:

[0058] forming the first positive electrode active layer on at least one surface of the positive electrode current collector;

[0059] The second positive electrode active layer is formed on a surface of the first positive electrode active layer away from the positive electrode current collector.

[0060] A fourth aspect of the present application provides an electrical device comprising at least one of the battery provided in the first aspect and the positive electrode plate provided in the second aspect.

[0061] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. The details of one or more embodiments of the present application are presented in the following drawings and descriptions. Other features, purposes and advantages of the present application will become apparent from the specification, drawings and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0063] Figure 1 This is a schematic diagram of a positive electrode sheet according to one embodiment of the present application.

[0064] Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.

[0065] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown.

[0066] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.

[0067] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0068] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0069] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0070] Figure 8 This is a cross-sectional scanning electron microscope image of the positive electrode sheet prepared in Example 2 of the present application.

[0071] Description of reference numerals:

[0072] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module; 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate; 531. Positive electrode sheet; 5311. Positive current collector; 5312. First positive electrode active layer; 5313. Second positive electrode active layer; 6. Electrical device. DETAILED DESCRIPTION

[0073] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0074] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.

[0075] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0076] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0077] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.

[0078] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0079] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0080] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.

[0081] Current batteries have difficulty in achieving high energy density, cycle performance, and power performance.

[0082] Ternary lithium batteries are significantly better than lithium iron phosphate batteries in terms of energy density. Due to the higher energy density of ternary materials, ternary lithium batteries can provide electric vehicles with longer driving range. This is an important consideration for electric vehicles that pursue high performance and long driving range. However, ternary materials have the problem of large cycle expansion force and increased cycle impedance DCR at low and medium SOC (state of charge), which leads to a significant deterioration in power performance stability.

[0083] Therefore, how to make the battery have good energy density, cycle performance and power performance stability is a technical problem that needs to be solved urgently.

[0084] Based on this, the present application provides a battery, a positive electrode plate and a preparation method thereof, and an electrical device, aiming to improve the energy density, cycle performance and power performance stability of the battery.

[0085] The battery, positive electrode sheet and electrical device according to one embodiment of the present application are described below with appropriate reference to the drawings.

[0086] In some embodiments, the battery is a secondary battery, further a lithium-ion battery.

[0087] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0088] Positive electrode

[0089] The positive electrode plate includes a positive current collector, a first positive active layer and a second positive active layer. The first positive active layer is disposed on at least one surface of the positive current collector, and the first positive active layer includes a ternary material A and a lithium iron phosphate material, wherein the Dv50 particle size of the ternary material A is greater than the Dv50 particle size of the lithium iron phosphate material; and / or the Dn50 particle size of the ternary material A is greater than the Dn50 particle size of the lithium iron phosphate material. The second positive active layer is disposed on a surface of the first positive active layer away from the positive current collector, and the second positive active layer includes a ternary material B.

[0090] Furthermore, both the ternary material A and the ternary material B include nickel elements, and the molar content of the nickel element in the ternary material A in the total amount of the ternary metal is higher than the molar content of the nickel element in the ternary material B in the total amount of the ternary metal.

[0091] In the positive electrode sheet, the types of ternary material A and ternary material B may be the same or different.

[0092] Dv50 is a well-known meaning in the art and can be measured by methods known in the art, for example, using a laser particle size analyzer (such as Malvern Master Size 3000). Dv50 represents the particle size corresponding to the cumulative volume distribution percentage of particles from the smallest particle size to 50% according to the particle size volume distribution.

[0093] The particle size volume distribution can be obtained by the following method: take a clean beaker, add an appropriate amount of the sample to be tested, and fully ultrasonicate to ensure that the sample is completely dispersed. The test instrument is Malvern 2000 of the United States. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light (shading degree: 8-12%). Draw a particle size volume distribution diagram based on the test data.

[0094] It should be noted that in the present application, in the preparation process of the positive electrode plate, the Dv50 particle size of the ternary material A can be controlled to be larger than the Dv50 particle size of the lithium iron phosphate material. When the Dv50 particle size of the ternary material A and the Dv50 particle size of the lithium iron phosphate material are reversely tested in the battery or the positive electrode plate, the active layer in the positive electrode plate can be peeled off and other materials are dissolved with a solvent to obtain the positive electrode active material, and then the Dv50 particle size is measured by a laser particle size analyzer (such as Malvern Master Size 3000); the above-mentioned Dv50 method can also be used for testing to obtain the Dv50 particle size of the positive electrode active material.

[0095] The Dn50 particle size (number average particle size) is well known in the art and can be measured using methods known in the art. For example, it can be measured using a laser particle size analyzer (such as Malvern Master Size 3000). Wherein, Dn50 represents the average particle size in terms of number, which is obtained by first multiplying the number of particles of each particle size by its particle size, then adding all the products, and then dividing by the total number of particles, thereby obtaining the average particle size weighted by number.

[0096] The Dn50 particle size (number average particle size) can be obtained by the following method: Take a clean beaker, add an appropriate amount of the sample to be tested, and fully ultrasonicate to ensure that the sample is completely dispersed. The test instrument is Malvern 2000 of the United States. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the number average particle size of the particles can be obtained by receiving and measuring the energy distribution of the scattered light (shading degree: 8-12%).

[0097] It should be noted that in the present application, in the preparation process of the positive electrode plate, the Dn50 particle size of the ternary material A can be controlled to be larger than the Dn50 particle size of the lithium iron phosphate material. When the Dn50 particle size of the ternary material A and the Dn50 particle size of the lithium iron phosphate material are reversely tested in the battery or the positive electrode plate, the testing can be carried out by the following method.

[0098] The following method can be used to detect the Dn50 particle size (number average particle size) of the positive electrode active material in the positive electrode sheet of the battery:

[0099] The positive electrode sheet is subjected to ion milling CP slicing to obtain a cross section (a cross section obtained by slicing along the thickness direction), and the cross section is subjected to optical photograph tests such as SEM (scanning electron microscope), and the cross sections of the first positive electrode active layer and the second positive electrode active layer are respectively subjected to the following tests:

[0100] Take any five areas of the positive electrode active material particles of the same size and shape (the actual size is a square sampling area of ​​15μm x 30μm) in the same scanning electron microscope (SEM) at 10kv and 30k magnification for observation. In this detection process, the characteristic elements of the positive electrode active material particles can be detected in combination with EDS to identify whether the positive electrode active material particles are ternary materials or lithium iron phosphate.

[0101] The particle size of each positive electrode active material particle (ternary material or lithium iron phosphate) within the square sampling area is tested, where the particle size of each positive electrode active material particle (ternary material or lithium iron phosphate) refers to the longest diameter of the particle; and the number of particles of each particle size of the ternary material or lithium iron phosphate within the square sampling area is multiplied by its particle size, and then all products are added and divided by the total number of particles to obtain the average particle size with quantity as the weight, which is the Dn50 particle size of the ternary material or lithium iron phosphate in the area. Then the Dn50 particle sizes of the five areas are averaged to obtain the Dn50 particle size of the ternary material or lithium iron phosphate in the positive electrode sheet.

[0102] Therefore, the present application adopts a two-layer positive electrode active layer structure design, and the second positive electrode active layer of the upper layer adopts ternary material B to provide good energy density, and the lithium ion transmission speed of the ternary material is faster, and the ternary material B is located in the second positive electrode active layer of the upper layer to provide good cycle performance; on this basis, the first positive electrode active layer of the lower layer adopts ternary material A with a larger particle size and lithium iron phosphate material with a smaller particle size, and the two positive electrode active materials with different particle sizes and different types are mixed and graded, which can improve the compaction density of the first positive electrode active layer, so that the lower layer and the upper positive electrode active layer can have a good compaction density match to give play to the energy density advantage of the ternary material, and at the same time, lithium iron phosphate is added to the first positive electrode active layer of the lower layer, and lithium iron phosphate is an olivine structure, and its lattice structure is stable and not easy to collapse and cause material loss, so the cycle impedance of the first positive electrode active layer of the lower layer is low, and because the voltage platform of lithium iron phosphate is lower, thanks to the elongation of the Fe platform, the power performance of the battery in medium and low SOC states is significantly improved, which makes up for the disadvantage that the battery uses a single ternary material and the DCR increases rapidly in the low SOC state. Ternary materials with higher nickel content have higher specific capacity. The increase in nickel content can improve the reversible lithium insertion capacity of the ternary material, thereby increasing the energy density of the battery. However, as the nickel content of the ternary material increases, its alkalinity increases, its water absorption increases, and its side reactions increase, which will also lead to an increase in DCR. Further setting the ternary material A with a higher nickel content in the first positive electrode active layer of the lower layer can make up for the problem of increased DCR caused by the higher nickel content of the ternary material A, so as to improve the energy density while taking into account good power performance. Ternary material B with a lower nickel content has a better advantage in high voltage resistance, and has fewer side reactions than high-nickel ternary materials, which is beneficial to reduce the DCR of the battery.

[0103] Therefore, the above-mentioned positive electrode plate of the present application is applied to the battery, which can make the battery have good energy density, cycle performance and power performance stability.

[0104] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0105] In the present application, the Dv50 particle size of the ternary material A is greater than the Dv50 particle size of the lithium iron phosphate material, and the Dn50 particle size of the ternary material A is greater than the Dn50 particle size of the lithium iron phosphate material, both of which can achieve similar technical effects.

[0106] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0107] See also Figure 1 The positive electrode sheet 531 of one embodiment includes a positive current collector 5311, a first positive active layer 5312 and a second positive active layer 5313. The first positive active layer 5312 is disposed on both surfaces of the positive current collector 5311, and the second positive active layer 5313 is disposed on the surfaces of the first positive active layer 5312 on both sides away from the positive current collector 5311. It can be understood that the first positive active layer 5312 and the second positive active layer 5313 stacked above can also be disposed on only one surface of the positive current collector 5311.

[0108] The larger the particle size of the positive electrode active material in the positive electrode active layer, the larger the gap between the positive electrode active material particles in the positive electrode active layer, and the greater the migration resistance of lithium ions inside the positive electrode active material particles, which leads to an increase in the solid phase impedance of the positive electrode active layer; in addition, the increase in the gap between the positive electrode active material particles will also reduce the compaction density of the electrode sheet, thereby affecting the energy density of the battery. The smaller particle size of the positive electrode active material usually helps to shorten the diffusion path of lithium ions, reduce the migration resistance of lithium ions inside the positive electrode active material particles, and thus reduce the solid phase impedance, improve the conductivity of the positive electrode active layer and the power performance of the battery. However, the smaller the particle size of the positive electrode active material, the larger the specific surface area of ​​the positive electrode active material particles, the higher the probability of side reactions of the functional groups on the surface of the positive electrode active material particles, and the increase in the DCR (direct current internal resistance) of the battery. Therefore, the particle size of the positive electrode active material particles in the positive electrode active layer needs to be controlled within an appropriate range, so that the impedance of lithium ions inside the positive electrode active material particles is low and the positive electrode active layer has an appropriate compaction density, thereby improving the conductivity and compaction density of the positive electrode active layer, so that the battery can further have good energy density, cycle performance and power performance.

[0109] In some embodiments, the difference between the Dv50 particle size of the ternary material A and the Dv50 particle size of the lithium iron phosphate material is between 0.8μm and 4μm. As examples, it can be 0.8μm, 1μm, 1.5μm, 2μm, 2.4μm, 2.5μm, 2.8μm, 3μm, 3.4μm, 3.5μm, 4μm. It can also be within the range formed by any two of the above point values ​​as end values, which can be selected as 2.8μm to 3.5μm.

[0110] In some embodiments, the difference between the Dn50 particle size of the ternary material A and the Dn50 particle size of the lithium iron phosphate material is between 0.8μm and 4μm. As examples, it can be 0.8μm, 1μm, 1.5μm, 2μm, 2.4μm, 2.5μm, 2.8μm, 3μm, 3.4μm, 3.5μm, 4μm. It can also be within the range formed by any two of the above point values ​​as end values, which can be selected as 2.8μm to 3.5μm.

[0111] Controlling the difference between the Dv50 particle size or Dn50 particle size of the ternary material A and the lithium iron phosphate material within the above range can make the battery further have good energy density, cycle performance and power performance. In some embodiments, the Dv50 particle size of the ternary material A is 2μm~5.2μm. As an example, the Dv50 particle size of the ternary material A can be 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.2μm. Furthermore, the Dv50 particle size of the ternary material A can be 3μm~4.2μm, or it can be within the range consisting of any two of the above point values ​​as end values, and the following is similar.

[0112] In some embodiments, the Dn50 particle size of the ternary material A in the first positive electrode active layer is 2 μm to 7.2 μm. As an example, the Dn50 particle size of the ternary material A can be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.2 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.2 μm. Further, the Dn50 particle size of the ternary material A can be 3 μm to 6.2 μm, 4 μm to 7.2 μm or 4 μm to 6.2 μm, or it can be within the range formed by any two of the above point values ​​as end values.

[0113] In the present application, the Dv50 particle size of the ternary material A is 2 μm to 5.2 μm, which is equivalent in technical effect to the Dn50 particle size of the ternary material A being 2 μm to 7.2 μm. Furthermore, in the present application, when the Dv50 particle size of the ternary material A is 2 μm to 5.2 μm, the Dn50 particle size of the ternary material A is in the range of 2 μm to 7.2 μm.

[0114] In the present application, the Dv50 particle size of the ternary material A is 3 μm to 4.2 μm, which is equivalent in technical effect to the Dn50 particle size of the ternary material A being 3 μm to 6.2 μm. Furthermore, in the present application, when the Dv50 particle size of the ternary material A is 3 μm to 4.2 μm, the Dn50 particle size of the ternary material A is in the range of 3 μm to 6.2 μm.

[0115] The Dv50 particle size or Dn50 particle size of the ternary material A is within the above range, so that the gaps between the ternary material particles in the first positive electrode active layer are within a relatively suitable range, the impedance of lithium ions inside the positive electrode active material particles is low and the positive electrode active layer has a suitable compaction density, thereby improving the conductivity and compaction density of the positive electrode active layer, thereby enabling the battery to further have good energy density, cycle performance and power performance.

[0116] In some embodiments, the ternary material A includes polycrystalline particles. Single crystal particles are particles inside the crystal that are regularly and periodically arranged in three-dimensional space. Polycrystalline particles refer to a collection of single crystals of many oriented grains. After the polycrystalline ternary material A is matched with lithium iron phosphate, during the charge and discharge process, the potential difference between the particles is smaller when lithium ions are released, the internal anion crosstalk of the positive electrode is smaller, the loss of positive electrode active materials is less, and the long-term cycle performance is better.

[0117] The Dv50 particle size or Dn50 particle size of lithium iron phosphate is relatively small. If lithium iron phosphate is used alone as the positive electrode active material of the lower layer, the compaction density of the lower layer is low. The first positive electrode active layer of the lower layer of the present application adopts a ternary material of polycrystalline particles with a larger particle size and a gradation of lithium iron phosphate with a smaller particle size, which is conducive to improving the compaction density of the first positive electrode active layer of the lower layer, making the compaction density between the first positive electrode active layer of the lower layer and the second positive electrode active layer of the upper layer better matched, obtaining good energy density, while taking into account good power performance.

[0118] In some embodiments, the Dv50 particle size of the lithium iron phosphate material is 0.8 μm to 1.8 μm. As an example, the Dv50 particle size of the lithium iron phosphate material can be 0.8 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm. Further, the Dv50 particle size of the lithium iron phosphate material can be 1.0 μm to 1.5 μm, or can be within the range formed by any two of the above point values ​​as end values.

[0119] In some embodiments, the Dn50 particle size of the lithium iron phosphate material in the first positive electrode active layer is 0.8 μm to 3.8 μm. As an example, the Dn50 particle size of the lithium iron phosphate material can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.5 μm, 2.8 μm, 3 μm, 3.5 μm, 3.8 μm. Further, the Dn50 particle size of the lithium iron phosphate material can be 1.0 μm to 3.5 μm, or it can be within the range formed by any two of the above point values ​​as end values.

[0120] The Dv50 particle size or Dn50 particle size of the lithium iron phosphate material is within the above range, and it is matched with the ternary material A in the above particle size range, so that the small particle size of the lithium iron phosphate material can be more fully filled in the gap between the large particles, which can further improve the compaction density of the lower layer and make the compaction density between the lower active layer and the upper active layer better matched. In addition, the Dv50 particle size or Dn50 particle size of the lithium iron phosphate material is within the above smaller range, Li + The smaller the transmission path, the higher the conductivity of the first positive electrode active layer, the better the battery's kinetics, and the better the battery's power performance, thereby enabling the battery to have good energy density, cycle performance, and power performance.

[0121] Furthermore, the lithium iron phosphate material includes single crystal particles. Since the single crystal particles have a perfect crystal structure or few defects, the migration resistance of lithium ions in the solid phase of the single crystal particles is small, thereby reducing the solid phase impedance, which is conducive to the lower layer inhibiting the growth of DCR under low and medium SOC, thereby improving the power performance of the battery.

[0122] In some embodiments, the lithium iron phosphate material includes one or more of lithium iron phosphate bulk particles, lithium iron phosphate bulk particles coated by a coating layer, and their respective doping and modification materials. Wherein, the lithium iron phosphate bulk particles refer to lithium iron phosphate particles that have not been coated or doped or otherwise modified.

[0123] Furthermore, the coating layer includes but is not limited to carbon coating. In some embodiments, in the first positive electrode active layer, the mass proportion of the lithium iron phosphate material in the total amount of the lithium iron phosphate material and the ternary material A is 50% to 95%. As an example, in the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or it can be within the range consisting of any two of the above point values ​​as end values.

[0124] Furthermore, in the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 60% to 80%, or can be within the range formed by any two of the above point values ​​as end values. The mass proportion of the lithium iron phosphate material is within the above range, so that more lithium iron phosphate material can be more fully filled in the gaps between large particles, and the role of lithium iron phosphate in reducing DCR at low and medium SOC during the life cycle is more fully utilized, thereby improving the power performance of the battery.

[0125] The positive electrode sheet is ion-milled and CP-sliced ​​to obtain a cross-section, and the cross-section is subjected to optical photograph tests such as SEM (scanning electron microscope). The element distribution results obtained by EDS detection of a rectangular sampling area with an actual cross-section size of 15 microns by 30 microns are used to identify the relative distribution mass of lithium iron phosphate and ternary material in the sampling area. In this way, the mass proportion of lithium iron phosphate in the total mass of ternary material A and lithium iron phosphate can be detected.

[0126] In some embodiments, the Dv50 particle size of the ternary material B is 4 μm to 13 μm. As an example, the Dv50 particle size of the ternary material B can be 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 9.4 μm, 9.5 μm, 10 μm, 11 μm, 12 μm, 13 μm, or can be within the range formed by any two of the above point values ​​as end values. Further, the Dv50 particle size of the ternary material B can be 8 μm to 11 μm.

[0127] In some embodiments, the Dn50 particle size of the ternary material B in the upper second positive electrode active layer is 4μm~15μm. As an example, the Dn50 particle size of the ternary material B can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 9.4μm, 9.5μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or it can be within the range formed by any two of the above point values ​​as end values. Further, the Dn50 particle size of the ternary material B can be 8μm~13μm.

[0128] In the present application, the Dv50 particle size of the ternary material B is 4 μm to 13 μm, which is equivalent in technical effect to the Dn50 particle size of the ternary material B being 4 μm to 15 μm. Furthermore, in the present application, when the Dv50 particle size of the ternary material B is 4 μm to 13 μm, the Dn50 particle size of the ternary material B is in the range of 4 μm to 15 μm.

[0129] In the present application, the Dv50 particle size of the ternary material B is 8 μm to 11 μm, which is equivalent in technical effect to the Dn50 particle size of the ternary material B being 8 μm to 13 μm. Furthermore, in the present application, when the Dv50 particle size of the ternary material B is 8 μm to 11 μm, the Dn50 particle size of the ternary material B is in the range of 8 μm to 13 μm.

[0130] The Dv50 particle size or Dn50 particle size of the ternary material B in the upper second positive electrode active layer is within the above range, so that the gaps between the ternary material particles in the second positive electrode active layer are within a more appropriate range, the impedance of lithium ions inside the positive electrode active material particles is low and has a suitable compaction density, thereby improving the conductivity and compaction density of the second positive electrode active layer, so that the battery can further have good energy density, cycle performance and power performance. In addition, the battery can also achieve 4C fast charging performance and have a good cycle life, and the life can be ≥3000cls. Furthermore, the ternary material B includes single crystal particles. The ternary material B using single crystal particles has few surface defects and provides good cycle performance.

[0131] In some embodiments, the thickness of the first positive electrode active layer is less than that of the second positive electrode active layer. In this way, the second positive electrode active layer is mainly used, and the first positive electrode active layer is supplemented. The second positive electrode active layer of the upper layer is used as the main active layer to provide the main performance of high energy density and cycle performance of the battery cell; the first positive electrode active layer of the lower layer is used as an auxiliary. When the battery cell is discharged at a low SOC, since the second positive electrode active layer of the upper layer is close to a fully embedded state, the main lithium embedding process is in the first positive electrode active layer of the lower layer. The dynamics of the first positive electrode active layer of the lower layer directly affects the low SOC power of the battery cell. Therefore, the thickness of the first positive electrode active layer of the lower layer is controlled to be smaller, and the dynamics of the first positive electrode active layer of the lower layer is improved. With the use of the battery, the SOC dynamics advantage (low impedance) of the positive electrode sheet will become more and more obvious, reducing the DCR at low and medium SOCs during the life cycle, thereby improving the power performance of the battery.

[0132] In the present application, the first positive electrode active layer and the second positive electrode active layer can see a clear interface by taking optical photographs such as SEM (scanning electron microscope) of the cross section of the positive electrode plate; then the thickness of the first positive electrode active layer and the second positive electrode active layer at 10 positions of the cross section is measured, and the average value of the 10 thickness measurement values ​​is taken to obtain the thickness of the first positive electrode active layer and the second positive electrode active layer.

[0133] In some embodiments, the thickness of the first positive electrode active layer is between 15 μm and 150 μm. As an example, the thickness of the first positive electrode active layer can be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm.

[0134] Furthermore, the thickness of the first positive electrode active layer can be 30 μm to 60 μm, or can be within the range formed by any two of the above point values ​​as end values. When the thickness of the first positive electrode active layer is within this range, it can have better ion conductivity, thereby further improving the power performance of the battery.

[0135] In some embodiments, the thickness of the second positive electrode active layer is between 20 μm and 200 μm. As an example, the thickness of the second positive electrode active layer can be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, or 150 μm.

[0136] Furthermore, the thickness of the second positive electrode active layer can be 70 μm to 100 μm, or can be within the range formed by any two of the above points as end values. The thickness of the second positive electrode active layer within this range can further improve the power performance of the battery.

[0137] In some embodiments, ternary material A and ternary material B each independently include at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material.

[0138] In some embodiments, the molar content of nickel in the ternary material A is between 33% and 90% of the total amount of the ternary metal. As an example, the molar content of nickel in the ternary material A can be 33%, 1 / 3, 50%, 55%, 60%, 65%, 68%, 70%, 75%, 80%, 85%, 90% of the total amount of the ternary metal.

[0139] LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ) as an example, the molar content of nickel element in the total amount of ternary metal is 0.5, that is, 50%; ternary metal refers to nickel, cobalt and manganese ternary metal.

[0140] Furthermore, the molar content of nickel element in ternary material A in the total amount of ternary metal is between 70% and 90%, and can also be within the range formed by any two of the above-mentioned point values ​​as end values. Ternary materials with higher nickel content have higher specific capacity. The increase in nickel content can increase the reversible lithium insertion capacity of the ternary material, thereby increasing the energy density of the battery. However, as the nickel content of the ternary material increases, its alkalinity increases, its water absorption increases, and side reactions increase, which also leads to an increase in DCR. Therefore, the ternary material A with a higher nickel content is arranged in the first positive electrode active layer of the lower layer, and the ternary material A with a smaller particle size is used, which can make up for the problem of increased DCR caused by the nickel content of the ternary material A, so as to improve the energy density while taking into account good power performance.

[0141] In some embodiments, the molar content of nickel in the ternary material B is 33% to 90% of the total amount of the ternary metal. As an example, the molar content of nickel in the ternary material B can be 33%, 1 / 3, 50%, 55%, 60%, 65%, 68%, 70%, 75%, 80%, 85%, 90% of the total amount of the ternary metal.

[0142] Furthermore, the molar content of nickel in the ternary material B is between 33% and 50% of the total ternary metal content. Ternary material B within this range has a better high voltage resistance advantage, and its nickel content is moderate, and compared with high-nickel ternary materials, there are fewer side reactions, which is beneficial to reducing the DCR of the battery.

[0143] Non-limiting examples of nickel-cobalt-manganese ternary materials may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.68 Co 0.10 Mn 0.22 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 )、LiNi 0.9 Co0.05 Mn 0.05 O2 (also referred to as NCM 9055 ) etc. Non-limiting examples of nickel-cobalt-aluminum ternary materials may include LiNi 0.8 Co 0.15 Al 0.05 O2.

[0144] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode active material is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode active material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode active materials is also within the scope of positive electrode active materials. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include coating modification.

[0145] In the list of positive electrode active materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.

[0146] In some embodiments, the first positive electrode active layer and the second positive electrode active layer may further optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0147] In some embodiments, the first positive electrode active layer and the second positive electrode active layer may further include a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0148] In some embodiments, the method for preparing the positive electrode sheet may include the following steps S10-S20:

[0149] S10, forming a first positive electrode active layer on at least one surface of the positive electrode current collector.

[0150] S20, forming a second positive electrode active layer on a surface of the first positive electrode active layer away from the positive electrode current collector.

[0151] Specifically, a first positive electrode slurry and a second positive electrode slurry can be formed respectively, and then the first positive electrode slurry and the second positive electrode slurry are sequentially coated on at least one side surface of the positive electrode collector, and after drying, cold pressing and other processes, a positive electrode sheet can be obtained.

[0152] Furthermore, after the first positive electrode slurry is applied, the second positive electrode slurry is applied after drying.

[0153] The first positive electrode slurry can be formed by dispersing the components for preparing the first positive electrode active layer, such as the positive electrode active material (including the ternary material A and the lithium iron phosphate material), the conductive agent, the binder and any other components in a solvent.

[0154] The second positive electrode slurry may be formed by dispersing the components for preparing the second positive electrode active layer, such as the positive electrode active material (including the ternary material B), the conductive agent, the binder and any other components in a solvent.

[0155] Furthermore, the study found that the binder tends to float during the drying process. Therefore, in order to ensure that the content of the upper and lower layers of binder is evenly distributed in the product, the binder content added to the slurry of the lower first positive electrode active layer is slightly higher; in this way, the binder content in the entire positive electrode film layer is more uniform.

[0156] Furthermore, the mass content of the binder in the slurry of the first positive electrode active layer is greater than the mass content of the binder in the slurry of the second positive electrode active layer; specifically, the difference between the mass content of the binder in the slurry of the first positive electrode active layer and the mass content of the binder in the slurry of the second positive electrode active layer may be 0.5%~2%. As an example, it may be 0.5%, 1%, 1.5%, 2%, or within the range formed by any two of the above point values.

[0157] The type of solvent may be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The positive electrode slurry may be coated on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector.

[0158] Furthermore, the solid content of the first positive electrode slurry may be 40 wt % to 80 wt %.

[0159] Further, the solid content of the second positive electrode slurry may be 40 wt% to 80 wt%. As an example, the solid content of the first positive electrode slurry and the solid content of the second positive electrode slurry may be 40 wt%, 50 wt%, 55 wt%, 60 wt%, 64 wt%, 65 wt%, 70 wt%, 74 wt%, 75 wt%, 80 wt%, or within a range consisting of any two of the above point values ​​as end values.

[0160] Optionally, the solid content of the first positive electrode slurry is 64wt%~74wt%; the solid content of the second positive electrode slurry is 60wt%~70wt%.

[0161] When the first positive electrode slurry and the second positive electrode slurry are coated, the coating unit area density based on dry weight (excluding solvent) can be 15 mg / cm 2 ~35mg / cm 2 The compaction density of the positive electrode can be 3.0g / cm 3 ~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 .

[0162] Negative electrode

[0163] The negative electrode plate includes a negative electrode current collector. Further, the negative electrode plate may also include a negative electrode active layer disposed on at least one surface of the negative electrode current collector, and the negative electrode active layer includes a negative electrode active material.

[0164] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0165] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0166] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0167] In some embodiments, the negative electrode active layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0168] In some embodiments, the negative electrode active layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0169] In some of the embodiments, the negative electrode active layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0170] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode current collector coated with the negative electrode slurry can be on a single surface of the negative electrode current collector or on both surfaces of the negative electrode current collector.

[0171] The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000~10000mPa·s. When the negative electrode slurry is applied, the coating unit surface density based on dry weight (excluding solvent) can be 75~220 g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8 g / cm 3 .

[0172] Electrolytes

[0173] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0174] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0175] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0176] In some of the embodiments, the solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate, fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0177] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0178] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.

[0179] Isolation film

[0180] In some embodiments, the secondary battery further includes a separator.

[0181] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0182] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0183] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0184] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.

[0185] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0186] The secondary battery includes at least one battery cell. The secondary battery may include one or more battery cells.

[0187] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.

[0188] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell shown is an example of a battery cell with a square structure.

[0189] In some of the embodiments, the battery cell 5 may include an outer package. The outer package may be used to encapsulate the electrode assembly and the electrolyte. In some of the embodiments, the outer package of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0190] In some of these embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.

[0191] In some embodiments, the secondary battery may be a battery module or a battery pack. The battery module includes at least one battery cell. The number of battery cells contained in the battery module may be one or more, and those skilled in the art may select a suitable number according to the application and capacity of the battery module.

[0192] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0193] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0194] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.

[0195] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0196] In addition, one embodiment of the present application further provides an electrical device, which includes the above-mentioned secondary battery provided in the present application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.

[0197] As an electrical device, a secondary battery can be selected according to its usage requirements.

[0198] Figure 7 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0199] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.

[0200] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0201] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0202] Example 1

[0203] 1) Preparation of positive electrode

[0204] The positive electrode active material polycrystalline LiNi 0.8 Co 0.10 Mn 0.1 O2(NCM 811The ternary material A), lithium iron phosphate (single crystal particles), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are evenly mixed in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 29.2:68.0:0.7:2.1 to obtain a first positive electrode slurry.

[0205] The specific values ​​of Dv50 particle size of ternary material A and lithium iron phosphate are shown in Table 1. In the total mass of ternary material A and lithium iron phosphate, the mass proportion of lithium iron phosphate is K, and the specific value is shown in Table 1. 0.5 Co 0.2 Mn 0.3 O2(NCM 523 , ternary material B), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed uniformly in an appropriate amount of solvent N-methylpyrrolidone (NMP) according to a mass ratio of 96.2:2.7:1.1 to obtain a second positive electrode slurry. The specific value of the Dv50 particle size of ternary material B is shown in Table 1.

[0206] The first positive electrode slurry is coated on the positive electrode collector aluminum foil and dried to form a first positive electrode active layer; the second positive electrode slurry is coated on the dried slurry surface to form a second positive electrode active layer, and the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes.

[0207] The overall compaction density of the positive electrode is 3.1g / cm 3 .

[0208] 2) Preparation of negative electrode

[0209] The negative electrode active material artificial graphite, conductive agent carbon black (Super P), binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) were mixed evenly in an appropriate amount of solvent deionized water at a mass ratio of 96.4:0.7:1.8:1.1 to obtain a negative electrode slurry; the negative electrode slurry was coated on the negative electrode current collector copper foil, and a single-sided thickness of 54μm was formed through drying, cold pressing, striping and cutting to obtain a negative electrode sheet. The compaction density of the negative electrode sheet is 1.75g / cm 3 .

[0210] 3) Isolation film

[0211] A 12μm thick polypropylene isolation film was selected.

[0212] 4) Preparation of electrolyte

[0213] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:70 to obtain an organic solvent, LiFSI accounting for 3 wt% of the entire electrolyte is dissolved in the mixed solvent, and fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.

[0214] 5) Preparation of secondary batteries

[0215] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the electrolyte is injected after drying. After vacuum packaging, standing, forming, shaping and other processes, a secondary battery is obtained; the ratio of the mass of the electrolyte to the capacity of the secondary battery (injection coefficient) is 2.4 g / Ah.

[0216] Embodiment 2-3

[0217] The preparation methods of the secondary batteries of Examples 2 to 3 are similar to those of the secondary battery of Example 1, except that the Dv50 of the ternary material B is different. Please refer to Table 1 for the specific differences.

[0218] Embodiment 4-5

[0219] The preparation methods of the secondary batteries of Examples 4 to 5 are similar to those of the secondary battery of Example 2, except that the Dv50 of the lithium iron phosphate material is different. Please refer to Table 1 for the specific differences.

[0220] Embodiment 6-7

[0221] The preparation methods of the secondary batteries of Examples 6 to 7 are similar to those of the secondary batteries of Example 2, except that the Dv50 of the ternary material A is different. Please refer to Table 1 for the specific differences.

[0222] Embodiment 8-9

[0223] The secondary batteries of Examples 8 to 9 are prepared in a similar manner to the secondary battery of Example 2, except that the mass proportion K of lithium iron phosphate in the total mass of the ternary material A and lithium iron phosphate is different. Please see Table 1 for the specific differences.

[0224] Embodiment 10-11

[0225] The secondary batteries of Examples 10 to 11 are prepared in a similar manner to the secondary battery of Example 2, except that at least one of the specific types of ternary material A and ternary material B is different. Please refer to Table 1 for the specific differences.

[0226] Comparative Example 1

[0227] The preparation method of the secondary battery of Comparative Example 1 is similar to that of the secondary battery of Example 2, except that the first positive electrode slurry is first coated on the positive electrode current collector aluminum foil, and then the second positive electrode slurry is coated, and other processes are the same; the formed positive electrode sheet is compared with Example 1, except that the positions of the first positive electrode active layer and the second positive electrode active layer in Example 1 are swapped.

[0228] The following is a performance test.

[0229] (1) Compacted density test of the entire electrode: disassemble the battery cell to take out the electrode, and punch it into 1540.25mm 2 Take another layer of electrode, wipe off the surface membrane layer, and punch out the remaining empty current collector foil into 1540.25mm 2 Take a small disc of aluminum foil and weigh the empty aluminum foil mass M0, then the compaction density PD=(M-M0) / 1.54025 / n / (L-L0), where n is the number of film layers coated on the current collector, which is 1 or 2, single-sided coating or double-sided coating. L0 is the thickness of the current collector foil.

[0230] (2) The positive electrode sheet of the obtained battery is sliced ​​and the cross section obtained is subjected to SEM (scanning electron microscope) testing.

[0231] The cross section of the positive electrode sheet prepared in Example 2 was subjected to SEM (scanning electron microscope) testing, and the obtained SEM image is as follows: Figure 8 shown.

[0232] from Figure 8 It can be seen that the interfaces between the positive electrode current collector 5311 (aluminum foil) and the first positive electrode active layer 5312 and between the first positive electrode active layer 5312 (lower layer) and the second positive electrode active layer 5313 (upper layer) of the positive electrode sheet are clearly visible. Figure 8 In the first positive electrode active layer 5312 of the middle and lower layer, the A frame contains ternary material A, the C frame contains lithium iron phosphate (LFP), and in the second positive electrode active layer 5313 of the upper layer, the B frame contains ternary material B.

[0233] Then the thickness of the first positive electrode active layer and the second positive electrode active layer at 10 positions of the cross section were measured, and the average value of the 10 thickness measurement values ​​was taken to obtain the thickness of the first positive electrode active layer and the second positive electrode active layer. The thickness of the first positive electrode active layer and the second positive electrode active layer were 20 μm and 30 μm, respectively.

[0234] The following method can be used to detect the Dn50 particle size (number average particle size) of the positive active material in the positive electrode sheet of the battery: ion mill the positive electrode sheet to obtain a cross section (a cross section obtained by slicing along the thickness direction), and perform optical photo tests such as SEM (scanning electron microscope) on the cross section. The following tests are performed on the cross sections of the first positive active layer and the second positive active layer respectively: observe the positive active material particles in any 5 areas of the same size and shape (the actual size is a square sampling area of ​​15μm by 30μm) in the same scanning electron microscope (SEM) at 10kv and 30k magnification. In this detection process, the characteristic elements of the positive active material particles can be combined with EDS to identify whether the positive active material particles are ternary materials or lithium iron phosphate.

[0235] The particle size of each positive electrode active material particle (ternary material or lithium iron phosphate) within the square sampling area is tested, where the particle size of each positive electrode active material particle (ternary material or lithium iron phosphate) refers to the longest diameter of the particle; and the number of particles of each particle size of the ternary material or lithium iron phosphate within the square sampling area is multiplied by its particle size, and then all products are added and divided by the total number of particles to obtain the average particle size with quantity as the weight, which is the Dn50 particle size of the ternary material or lithium iron phosphate in the area. Then the Dn50 particle sizes of the five areas are averaged to obtain the Dn50 particle size of the ternary material or lithium iron phosphate in the positive electrode sheet.

[0236] The Dn50 particle sizes of ternary material A, lithium iron phosphate material and ternary material B are obtained. The Dn50 particle size of ternary material A in Examples 1 to 11 is 2 μm to 7.2 μm, the Dn50 particle size of lithium iron phosphate material is 0.8 μm to 3.8 μm, and the Dn50 particle size of ternary material B is 4 μm to 15 μm.

[0237] The positive electrode sheet is ion-milled and CP sliced ​​to obtain a cross section, and the cross section is tested by optical photographs such as SEM (scanning electron microscope). The element distribution results obtained by EDS detection of a rectangular sampling area with an actual cross section size of 30 microns by 30 microns are used to identify the relative distribution mass of lithium iron phosphate and ternary materials in the sampling area, so that the mass proportion K of lithium iron phosphate in the total mass of ternary material A and lithium iron phosphate can be detected. The mass proportion K obtained is equivalent to the mass proportion K in Table 1.

[0238] (2) Energy density test.

[0239] At 25°C, the battery was charged at a constant current and constant voltage of 0.33C to the designed upper limit voltage, with a cut-off current of 0.05C. After standing for 30 minutes, it was discharged at 0.33C to the designed lower limit voltage. The discharge energy P (Wh) was recorded, and the cell volume was recorded as V (L). The energy density (Wh / L) = P / V.

[0240] The energy density in Example 1 is 510 Wh / L.

[0241] (3) DCR growth rate at medium and low SOC

[0242] Medium and low SOC refers to 0~30% SOC. The DCR value of the battery at medium and low SOC can better reflect the power performance of the battery. 20% SOC is used in this test.

[0243] The DCR growth rate under medium and low SOC can characterize the power performance attenuation of the battery under medium and low charge states. The greater the DCR growth rate under medium and low SOC, the greater the power performance attenuation of the battery under medium and low charge states, that is, the worse the power performance stability of the battery; on the contrary, the smaller the DCR growth rate under medium and low SOC, the smaller the power performance attenuation of the battery under medium and low charge states, that is, the better the power performance stability of the battery.

[0244] The test method of DCR of the battery is as follows: the prepared battery is charged to 4.4V at 0.1C in a 25°C environment, and then discharged at 0.33C for 144 minutes to adjust to 20% SOC. At this time, the voltage is recorded as V1. The battery is discharged at a current value of 4C for 10S, and the potential at this time is recorded as V2; DCR1 value = (V1-V2) / current value corresponding to 4C.

[0245] Continue to charge at 0.5C to 4.4V in a 25℃ environment, and then discharge at 0.33C to 2.5V. Repeat this charge and discharge cycle for 1000 times. Charge the cycled battery to 4.4V at 0.1C in a 25℃ environment, and then discharge at 0.33C for 144min to adjust to 20% SOC. At this time, the voltage is recorded as V3. Discharge at a current value of 4C for 10S, and the potential at this time is recorded as V4; DCR2 value = (V3-V4) / current value corresponding to 4C.

[0246] DCR growth rate at 20% SOC = (DCR2-DCR1) / DCR1.

[0247] (4) Cycle performance

[0248] The cycle performance is characterized by the number of cycles at which the capacity decays to 80% of the initial capacity at 25°C. The specific cycle process is as follows: the prepared battery is charged to 4.4V at 0.5C in a 25°C environment, and then discharged to 2.5V at 0.33C. The charge and discharge cycle is repeated until the capacity decays to 80% of the initial capacity. The number of cycles at this time is recorded (the unit digit is rounded to an integer multiple of 10), as shown in Table 1.

[0249] The test results of various embodiments and comparative examples are shown in Table 1.

[0250] Table 1

[0251]

[0252] The positive electrode plate of the present application has a double-layer active layer, and the lower layer adopts a mixed system of LFP and NCM, and the upper layer adopts NCM. Therefore, when the SOC of the battery is high, it is mainly NCM that provides lithium ions for discharge; when the SOC is low, it is mainly LFP that provides lithium ions for discharge.

[0253] Compared with Example 2, Comparative Example 1 uses the second positive electrode active layer containing ternary material B as the lower layer, and uses the first positive electrode active layer containing ternary material A and lithium iron phosphate as the upper layer. In this way, under the high SOC state of the lower second positive electrode active layer, the positive electrode plate is mainly delithiated by the lower ternary material B, and the ternary material B needs to pass through the upper active layer containing LFP for delithiation. The increase in lithium ion transmission path leads to an increase in impedance. At the same time, anion crosstalk is prone to occur at the positive electrode, which increases the loss of positive electrode material and thus reduces the cycle performance. In addition, the increase in impedance leads to an inconsistency with the negative electrode lithium insertion rate, which makes the negative electrode prone to lithium precipitation. Under low SOC, the positive electrode plate is over-delithiated, resulting in an increase in positive electrode material loss, which in turn leads to a decrease in cycle performance. In addition, the increase in lithium ion transmission path in the lower layer also increases the overall impedance.

[0254] Each embodiment has good energy density and low DCR growth rate, which shows that it can take into account good energy density, cycle performance and power performance stability.

[0255] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0256] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the scope of the claims.

Claims

1. A battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises: Positive electrode current collector; A first positive electrode active layer is provided on at least one surface of the positive electrode current collector, wherein the first positive electrode active layer comprises a ternary material A and a lithium iron phosphate material; the Dv50 particle size of the ternary material A is greater than the Dv50 particle size of the lithium iron phosphate material, and the difference between the Dv50 particle sizes of the ternary material A and the lithium iron phosphate material is in the range of 0.8 μm to 4 μm; and / or the Dn50 particle size of the ternary material A is greater than the Dn50 particle size of the lithium iron phosphate material, and the difference between the Dn50 particle size of the ternary material A and the Dn50 particle size of the lithium iron phosphate material is in the range of 0.8 μm to 4 μm; and, A second positive electrode active layer, disposed on a surface of the first positive electrode active layer away from the positive electrode current collector, wherein the second positive electrode active layer comprises a ternary material B; Among them, the ternary material A includes polycrystalline particles; in the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 55%~95%; the ternary material B includes single crystal particles; the thickness of the first positive electrode active layer is less than the thickness of the second positive electrode active layer; the ternary material A and the ternary material B both include nickel elements, and the molar content of the nickel element in the ternary material A in the total amount of ternary metals is higher than the molar content of the nickel element in the ternary material B in the total amount of ternary metals.

2. The battery according to claim 1, characterized in that Satisfy at least one of the following characteristics: (1) The Dv50 particle size of the ternary material A is 2 μm to 5.2 μm; (2) The Dn50 particle size of the ternary material A is 2 μm to 7.2 μm.

3. The battery according to claim 2, characterized in that The Dv50 particle size of the ternary material A is 3 μm to 4.2 μm, and / or the Dn50 particle size of the ternary material A is 3 μm to 6.2 μm.

4. The battery according to any one of claims 1 to 3, characterized in that Satisfy at least one of the following characteristics: (1) The Dv50 particle size of the lithium iron phosphate material is 0.8 μm to 1.8 μm, and / or the Dn50 particle size of the lithium iron phosphate material is 0.8 μm to 3.8 μm; (2) The lithium iron phosphate material includes single crystal particles; (3) The lithium iron phosphate material includes one or more of lithium iron phosphate bulk particles, lithium iron phosphate bulk particles coated by a coating layer, and their respective doping and modification materials.

5. The battery according to claim 4, characterized in that The Dv50 particle size of the lithium iron phosphate material is 1.0 μm to 1.5 μm, and / or the Dn50 particle size of the lithium iron phosphate material is 1 μm to 3.5 μm.

6. The battery according to any one of claims 1 to 3, characterized in that: In the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 60% to 95%.

7. The battery according to claim 6, characterized in that In the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 60% to 80%.

8. The battery according to any one of claims 1 to 3, characterized in that: Satisfy at least one of the following characteristics: (1) The Dv50 particle size of the ternary material B is 4 μm to 13 μm; (2) The Dn50 particle size of the ternary material B is 4 μm to 15 μm.

9. The battery according to claim 8, characterized in that The Dv50 particle size of the ternary material B is 8 μm to 11 μm, and / or the Dn50 particle size of the ternary material B is 8 μm to 13 μm.

10. The battery according to any one of claims 1 to 3, characterized in that Satisfy at least one of the following characteristics: (1) The thickness of the first positive electrode active layer is between 15 μm and 150 μm; (2) The thickness of the second positive electrode active layer is between 20 μm and 200 μm.

11. The battery according to any one of claims 1 to 3, characterized in that: The thickness of the first positive electrode active layer is between 30 μm and 60 μm.

12. The battery according to any one of claims 1 to 3, characterized in that The thickness of the second positive electrode active layer is between 70 μm and 100 μm.

13. The battery according to claim 1, characterized in that The ternary material A and the ternary material B each independently include at least one of a nickel-cobalt-manganese ternary material and a nickel-cobalt-aluminum ternary material.

14. The battery according to claim 13, characterized in that The nickel-cobalt-manganese ternary material includes LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.5 Co 0.25 Mn 0.25 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.68 Co 0.10 Mn 0.22 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2; The nickel-cobalt-aluminum ternary material includes LiNi 0.8 Co 0.15 Al 0.05 O2.

15. The battery according to claim 1, characterized in that Satisfy at least one of the following characteristics: (1) The molar content of nickel in the ternary material A is between 33% and 90% of the total amount of the ternary metal; (2) The molar content of nickel in the ternary material B is between 33% and 90% of the total amount of the ternary metal.

16. The battery according to claim 15, characterized in that Satisfy at least one of the following characteristics: (1) The molar content of nickel in the ternary material A is between 70% and 90% of the total amount of the ternary metal; (2) The molar content of nickel in the ternary material B is between 33% and 50% of the total amount of the ternary metal.

17. A positive electrode plate, characterized in that: include: Positive electrode current collector; A first positive electrode active layer is provided on at least one surface of the positive electrode current collector, wherein the first positive electrode active layer comprises a ternary material A and a lithium iron phosphate material; the Dv50 particle size of the ternary material A is greater than the Dv50 particle size of the lithium iron phosphate material, and the difference between the Dv50 particle sizes of the ternary material A and the lithium iron phosphate material is in the range of 0.8 μm to 4 μm; and / or the Dn50 particle size of the ternary material A is greater than the Dn50 particle size of the lithium iron phosphate material, and the difference between the Dn50 particle size of the ternary material A and the Dn50 particle size of the lithium iron phosphate material is in the range of 0.8 μm to 4 μm; and, A second positive electrode active layer, disposed on a surface of the first positive electrode active layer away from the positive electrode current collector, wherein the second positive electrode active layer comprises a ternary material B; Among them, the ternary material A includes polycrystalline particles; in the total amount of the lithium iron phosphate material and the ternary material A, the mass proportion of the lithium iron phosphate material is 55%~95%; the ternary material B includes single crystal particles; the thickness of the first positive electrode active layer is less than the thickness of the second positive electrode active layer; the ternary material A and the ternary material B both include nickel elements, and the molar content of the nickel element in the ternary material A in the total amount of ternary metals is higher than the molar content of the nickel element in the ternary material B in the total amount of ternary metals.

18. A method for preparing a positive electrode sheet, characterized in that: The positive electrode sheet is the positive electrode sheet as claimed in claim 17, and the preparation method comprises the following steps: forming the first positive electrode active layer on at least one surface of the positive electrode current collector; The second positive electrode active layer is formed on a surface of the first positive electrode active layer away from the positive electrode current collector.

19. An electrical device, characterized in that: Comprising at least one of the battery according to any one of claims 1 to 16 and the positive electrode sheet according to claim 17.

Citation Information

Patent Citations

  • Preparation method of power lithium ion battery

    CN112186259A

  • Positive plate and preparation method thereof, battery and power utilization device

    CN118335970A